High-performance flame-retardant aluminum composite plate and preparation method thereof

By using modified halogen-free flame retardant and special adhesives, the flame retardant performance and bonding strength of aluminum composite panels are improved, and the problems of insufficient flame retardant performance and adhesive stability of existing aluminum composite panels are solved. The high-performance flame-retardant aluminum composite panel is achieved, which is suitable for high fire resistance and durability requirements.

CN119217810AInactive Publication Date: 2024-12-31ALUBRIGHT IND CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411361380.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing aluminum composite panels lack flame retardant properties. The flame retardant is poor in compatibility when added to polypropylene core materials, which affects the mechanical properties, and the adhesive's bonding strength and heat and aging resistance are insufficient, resulting in limited application areas. .

Method used

Using modified halogen-free flame retardant and special adhesives, the flame retardant performance is improved by adding modified halogen-free flame retardant to the polypropylene core material and using modified penetrants and nanotitanium dioxide between aluminum composite panels. and bonding strength, the modified halogen-free flame retardant is formed of organosiloxane-modified diethyl aluminum hypophosphate, and the special adhesive contains ethylene-vinyl acetate copolymer and bisphenol A type epoxy resin, etc., through Hot press composite technology to prepare high-performance flame-retardant aluminum composite panels.

Benefits of technology

Achieve high-performance flame-retardant aluminum composite board with high fire resistance, stability and good adhesion, enhances the flame retardant effect and durability and flatness of aluminum composite board, and solves the problem that adhesives are susceptible to temperature difference. .

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of aluminum composite material preparation, and particularly discloses a high-performance flame-retardant aluminum composite plate and a preparation method thereof.The aluminum composite plate sequentially comprises an upper aluminum plate, a middle flame-retardant core material and a bottom aluminum plate from top to bottom, and all the layers are bonded through a special adhesive; the aluminum plate on the upper layer and the aluminum plate on the bottom layer are both aluminum alloy plates, and the thickness ranges from 0.5 mm to 0.8 mm. The high-performance flame-retardant aluminum composite plate disclosed by the invention has the advantages of better flame-retardant effect, high fireproof grade, good bonding among layers, high stability, light weight and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of aluminum composite material preparation, and specifically discloses a high-performance flame-retardant aluminum composite plate and a preparation method thereof. Background Art

[0002] Aluminum composite panels are composite panels composed of multiple layers of materials (the upper and lower layers are both high-purity aluminum alloy plates, and the middle layer is a non-toxic polypropylene plastic plate). Their surfaces are often coated with decorative and protective coatings or films as finishing layers. They have the advantages of economy, diversity, simple construction, and good processing performance. They have always attracted people's attention and favor, and have been widely used in the curtain wall design of high-rise buildings, and have achieved good results.

[0003] General aluminum composite panels have no flame retardant effect, and their core material polypropylene (PE) plastic board cannot meet the flame retardant requirements, which greatly limits their application areas. Based on this, flame retardant aluminum composite panels are a new type of decorative material that combines flame retardant properties with the characteristics of aluminum composite panels. Its surface has been specially treated and has good corrosion resistance, weather resistance and fire resistance, which can effectively delay the spread of fire in a fire. The flame retardant effect of flame retardant aluminum composite panels is generally brought by fireproof and flame retardant core materials. In the prior art, flame retardants are often directly added during the preparation of PE core materials. However, due to compatibility, the flame retardant effect cannot be fully exerted and may affect the mechanical properties of the aluminum composite panels.

[0004] The invention patent with publication number CN112848558A discloses a high-strength, lightweight, fireproof aluminum composite panel and its preparation process. The upper and lower layers of the fireproof aluminum composite panel are respectively aluminum alloy plate and aluminum alloy substrate, the middle layer is a flame-retardant core plate, the upper surface of the fireproof aluminum composite panel is provided with a protective film, and the lower surface of the fireproof aluminum composite panel is provided with a sound-absorbing layer; the sound-absorbing layer includes inner sound insulation felt, foam cotton layer, and outer sound insulation felt from inside to outside, and the cross section of the foam cotton layer is a honeycomb structure, wherein the flame-retardant core plate is mainly composed of the following components by mass: 65-75 parts of low-density polyethylene, 20-25 parts of modified hydrotalcite, 5-8 parts of expanded vermiculite powder, 3-5 parts of polyphosphoric acid amine, and 1-3 parts of antioxidant 1010. The aluminum composite panel has a fireproof grade of A1 and has excellent strength, impact and tensile properties. However, the layers are compounded by rolling, and the adhesives used for flame-retardant aluminum composite panels in the prior art often have problems such as low bonding strength and poor heat and aging resistance. The stability between the layers is poor and the long-term usability is poor.

[0005] In view of this, it is particularly important to disclose a high-performance flame-retardant aluminum composite panel. Summary of the invention

[0006] In view of the defects of the prior art, the present invention provides a high-performance flame-retardant aluminum composite panel and a preparation method thereof. The high-performance flame-retardant aluminum composite panel disclosed in the present invention has good flame retardant effect, high fireproof grade, good bonding between layers, high stability, and is light and durable.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] On the one hand, the present invention provides a high-performance flame-retardant aluminum composite panel, which comprises, from top to bottom, an upper aluminum plate, a flame-retardant core material in the middle layer, and a bottom aluminum plate, and each layer is bonded by a special adhesive; wherein the upper aluminum plate and the bottom aluminum plate are both aluminum alloy plates with a thickness of 0.5 to 0.8 mm.

[0009] Preferably, the thickness of the aluminum alloy plate is 0.65 mm.

[0010] In some embodiments of the present invention, the flame retardant core material of the middle layer comprises the following raw materials in parts by weight: 40-60 parts of polypropylene, 20-35 parts of modified halogen-free flame retardant, 0.5-3 parts of antioxidant 168, 0.1-2 parts of foaming agent, and 0.5-1 part of dispersant.

[0011] Preferably, the preparation steps of the flame retardant core material of the middle layer are as follows: add modified halogen-free flame retardant and dispersant into the reactor, stir, then add polypropylene, antioxidant 168 and foaming agent, mix evenly, and extrude and mold through a twin-screw extruder to obtain the flame retardant core material of the middle layer.

[0012] Preferably, the barrel temperature of the extrusion molding by the twin-screw extruder is 170-180°C, the die temperature is 165-175°C, and the gap is 2-3mm.

[0013] In some embodiments of the present invention, the preparation steps of the modified halogen-free flame retardant are as follows:

[0014] Add anhydrous ethanol and deionized water into the reactor, then add diethyl aluminum hypophosphite, stir and disperse, adjust the pH to 9-10, then add organosiloxane, heat to 40-60° C. under stirring, react for 1-3 hours, filter, wash, extract and dry the filtrate to obtain the modified halogen-free flame retardant.

[0015] In some embodiments of the present invention, the organosiloxane is a mixture of methyltriethoxysilane and tetraethoxysilane.

[0016] Preferably, the mass ratio of methyltriethoxysilane to tetraethoxysilane is 1:(0.8-1.2).

[0017] Further preferably, the mass ratio of methyltriethoxysilane to tetraethoxysilane is 1:1.

[0018] In some embodiments of the present invention, the mass ratio of diethylaluminum hypophosphite to organosiloxane is 10:(3-6).

[0019] Preferably, the mass ratio of diethylaluminum hypophosphite to organosiloxane is 10:4.5.

[0020] Preferably, the mass ratio of anhydrous ethanol to deionized water is (1-3):1.

[0021] Further preferably, the mass ratio of the anhydrous ethanol to deionized water is 2:1.

[0022] Preferably, the total amount of anhydrous ethanol and deionized water added is 2 to 4 times the mass of diethylaluminum hypophosphite.

[0023] The invention introduces organic siloxane methyltriethoxysilane and tetraethoxysilane of specific selection and proportion to modify diethyl aluminum hypophosphite, thereby obtaining a modified halogen-free flame retardant with high compatibility and stable flame retardant effect. This may be because the siloxane and silaneoxy groups on the organic siloxane are attached to the surface of diethyl aluminum hypophosphite through silanol groups to form hydrogen bonds, and at the same time, they are condensed with the hydroxyl groups on the surface of diethyl aluminum hypophosphite to form chemical bonds. At this time, the modified halogen-free flame retardant has strong hydrophobicity, and the surface has a certain degree of roughness due to the attachment of organic siloxane segments, which is conducive to the compatibility and combination of the modified halogen-free flame retardant with other components in the flame retardant core material system, and exerts a more efficient flame retardant effect.

[0024] In some embodiments of the present invention, the special adhesive comprises the following raw materials in parts by weight: 50-80 parts of ethylene-vinyl acetate copolymer, 2-5 parts of bisphenol A epoxy resin, 0.1-5 parts of styrene-maleic anhydride copolymer, 8-12 parts of rosin resin, 1-5 parts of paraffin, 5-10 parts of nano titanium dioxide, 0.5-2 parts of antioxidant 168 and 1-5 parts of modified penetrant.

[0025] Preferably, the preparation steps of the special adhesive are as follows:

[0026] Ethylene-vinyl acetate copolymer, bisphenol A epoxy resin, styrene-maleic anhydride copolymer, nano titanium dioxide and paraffin are mixed, heated to 100-120°C, stirred for 30-60 minutes, cooled to 50-60°C, and then modified penetrant, rosin resin and antioxidant 168 are added, heated to 70-90°C, stirred for 60-90 minutes, transferred to a twin-screw extruder, heated to 170-180°C for melt extrusion and granulation to obtain the special adhesive.

[0027] In some embodiments of the present invention, the preparation steps of the modified osmotic agent are as follows:

[0028] Add isooctyl alcohol polyoxyethylene ether into the reactor, heat to 50-60° C., then add a mixture of dimethyldichlorosilane and petroleum ether, react at a constant temperature for 1-1.5 hours, perform rotary evaporation and alkaline water washing, then add a water dispersion of bentonite, perform ultrasonic dispersion, stir and react at 40-60° C. for 5-15 minutes, cool to room temperature, wash with deionized water, and dry to obtain the modified penetrant.

[0029] In some embodiments of the present invention, the mass ratio of the polyoxyethylene isooctyl alcohol ether to the bentonite in the aqueous dispersion of bentonite is 10:(0.6-1).

[0030] Preferably, the mass ratio of the polyoxyethylene isooctyl alcohol ether to the bentonite in the aqueous dispersion of bentonite is 10:0.8.

[0031] In some embodiments of the present invention, the mass ratio of dimethyldichlorosilane in the petroleum ether mixture of isooctyl alcohol polyoxyethylene ether and dimethyldichlorosilane is 20:(1.4-1.7).

[0032] Preferably, the mass ratio of dimethyldichlorosilane in the petroleum ether mixture of isooctyl alcohol polyoxyethylene ether and dimethyldichlorosilane is 20:1.55.

[0033] Preferably, the concentration of dimethyldichlorosilane in the dimethyldichlorosilane-petroleum ether mixture is 10-15 wt %.

[0034] Further preferably, the concentration of dimethyldichlorosilane in the dimethyldichlorosilane-petroleum ether mixture is 12.5 wt %.

[0035] Preferably, the concentration of the aqueous dispersion of bentonite is 3-5 wt %.

[0036] More preferably, the concentration of the aqueous dispersion of bentonite is 4 wt %.

[0037] Preferably, the average particle size of the nano titanium dioxide is 5 to 10 nm.

[0038] As mentioned above, the present invention first performs flame retardant modification on the polypropylene core material to obtain a high-performance flame retardant core material, which effectively improves the flame retardant performance of the aluminum composite panel, improves the fire resistance level of the aluminum composite panel, and has good fireproof and heat insulation effects. However, when the aluminum composite panel is used as a decorative material for the exterior wall of a building, the existing adhesive has poor long-term bonding between the flame retardant core material and the aluminum alloy plate. The present invention prepares a special adhesive, which is specially added with a modified penetrant, and isooctanol polyoxyethylene ether is modified by introducing dimethyldichlorosilane and bentonite. The terminal hydroxyl groups of the isooctanol polyoxyethylene ether are capped with dimethyldichlorosilane, and silicon units are introduced into the penetrant molecules, which are then blended with bentonite. When it is added to the special adhesive The system is endowed with a stronger permeability and a moderate viscosity, which promotes the provision of a stable and high-strength bonding force between the layers of the aluminum composite panel, especially between the flame-retardant core material containing the modified halogen-free flame retardant and the aluminum composite panel, and has better adaptability. On the other hand, the bulging problem of the commonly used adhesives for aluminum composite panels, which is easily caused by the temperature difference between day and night, is solved. This may be because the hydroxyl group of the modified penetrant is blocked by the isooctyl alcohol polyoxyethylene ether, which improves the cohesive force of the modified penetrant. When it is added to the special adhesive system, the foaming phenomenon is significantly reduced. The introduction of bentonite also increases the fluidity of the system, which together promotes the uniform penetration of the special adhesive between the surfaces to be bonded on the aluminum composite panel, improves the flatness and long-term durability of the aluminum composite panel, and has excellent performance.

[0039] Preferably, the thickness of the flame retardant core material of the middle layer is 1.4-3 mm.

[0040] Further preferably, the thickness of the flame retardant core material of the middle layer is 2.2 mm.

[0041] On the other hand, the present invention also provides a method for preparing a high-performance flame-retardant aluminum composite panel, comprising the following steps: coating the upper and lower surfaces of the flame-retardant core material of the middle layer with a special adhesive, covering an aluminum plate on the upper surface of the flame-retardant core material of the middle layer to form an upper aluminum plate, covering another aluminum plate on the lower surface of the flame-retardant core material of the middle layer to form a bottom aluminum plate, and then hot-pressing and compounding to obtain the high-performance flame-retardant aluminum composite panel.

[0042] Preferably, the hot pressing composite operation is to press for 30 to 60 seconds at room temperature and a pressure of 50 to 80 MPa, then heat to 200 to 500° C., press for 60 to 120 seconds at a pressure of 100 to 300 MPa, and cool to room temperature while maintaining pressure.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] (1) The high-performance flame-retardant aluminum composite panel disclosed in the present invention has good flame-retardant effect, high fireproof grade, good bonding between layers, high stability, and is light and durable.

[0045] (2) The present invention modifies diethylaluminum hypophosphite by introducing specifically selected and proportioned organic silicone methyltriethoxysilane and tetraethoxysilane, thereby obtaining a modified halogen-free flame retardant with high compatibility, stable flame retardant effect, strong hydrophobicity and rough surface, thereby improving the binding and compatibility of the modified halogen-free flame retardant in the flame retardant core material system and exerting a more efficient flame retardant effect.

[0046] (3) The present invention prepares a special adhesive that can provide stable and high-strength bonding between the layers of the aluminum composite panel, especially between the flame-retardant core material containing the modified halogen-free flame retardant and the aluminum composite panel, and has good adaptability. On the other hand, it solves the problem that the commonly used adhesives for aluminum composite panels are easily affected by temperature differences, resulting in bulging, cracking and unreliable bonding, thereby improving the flatness and long-term durability of the aluminum composite panel. DETAILED DESCRIPTION

[0047] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0048] If not otherwise specified, the reagents used below can be easily obtained from commercial companies, among which the polypropylene model is PPK8003; the ethylene-vinyl acetate copolymer model is EVAV5110J; bisphenol A epoxy resin is purchased from Wuxi Jiunai Anticorrosion Materials Co., Ltd.; rosin resin is purchased from Puyang Kairuide Petroleum Resin Co., Ltd.; bentonite (particle size of 200 mesh) is purchased from Lingshou County Pengxian Mineral Products Processing Plant.

[0049] Unless otherwise specified, the foaming agents used in the following preparation examples are all azodicarbonamide, the dispersants used are all hexadecyltrimethylammonium bromide, and the average particle size of the nano-titanium dioxide used is 5 to 10 nm.

[0050] Preparation Example 1

[0051] The preparation steps of modified halogen-free flame retardant are as follows:

[0052] Add 100 mL of anhydrous ethanol and 50 mL of deionized water into the reactor, then add 50 g of diethylaluminum hypophosphite, stir and disperse, adjust the pH to 9.5, then add 11.25 g of methyltriethoxysilane and 11.25 g of tetraethoxysilane, heat to 50 ° C while stirring, react for 2 hours, filter, wash the filtrate with anhydrous ethanol 3 times, extract with anhydrous ethanol twice and dry at 60 ° C for 36 hours to obtain a modified halogen-free flame retardant.

[0053] Preparation Example 2

[0054] The preparation steps of the modified halogen-free flame retardant are the same as those of Preparation Example 1, except that 32.1 g of diethyl aluminum hypophosphite is added.

[0055] Preparation Example 3

[0056] The preparation steps of the modified halogen-free flame retardant are the same as those of Preparation Example 1, except that 9.4 g of methyltriethoxysilane and 13.1 g of tetraethoxysilane are added.

[0057] Preparation Example 4

[0058] The preparation steps of the modified halogen-free flame retardant are the same as those of Preparation Example 1, except that 22.5 g of methyltriethoxysilane and 0 g of tetraethoxysilane are added.

[0059] Preparation Example 5

[0060] The preparation steps of the modified halogen-free flame retardant are the same as those of Preparation Example 1, except that 0 g of methyltriethoxysilane and 22.5 g of tetraethoxysilane are added.

[0061] Preparation Example 6

[0062] The preparation steps of the flame retardant core material of the middle layer are as follows: add 27.5g of modified halogen-free flame retardant and 0.75g of dispersant into the reactor, stir at a speed of 800r / min, then add 50g of polypropylene, 1.75g ​​of antioxidant 168 and 1.05g of foaming agent, mix evenly, and extrude into shape through a twin-screw extruder at a barrel temperature of 170°C, a die temperature of 170°C, and a gap of 2.5mm to obtain the flame retardant core material of the middle layer.

[0063] The modified halogen-free flame retardant used in this preparation example is obtained from Preparation Example 1.

[0064] Preparation Example 7

[0065] The preparation steps of the flame retardant core material of the middle layer are as follows: add 20g of modified halogen-free flame retardant and 0.5g of dispersant into the reactor, stir at 600r / min, then add 40g of polypropylene, 0.5g of antioxidant 168 and 0.1g of foaming agent, mix evenly, and extrude into a flame retardant core material of the middle layer through a twin-screw extruder at a barrel temperature of 170°C, a die temperature of 165°C and a gap of 2mm to obtain the flame retardant core material of the middle layer.

[0066] The modified halogen-free flame retardant used in this preparation example is obtained from Preparation Example 1.

[0067] Preparation Example 8

[0068] The preparation steps of the flame retardant core material of the middle layer are as follows: add 35g of modified halogen-free flame retardant and 1g of dispersant into the reactor, stir at 1000r / min, then add 60g of polypropylene, 3g of antioxidant 168 and 2g of foaming agent, mix evenly, and extrude into a flame retardant core material of the middle layer through a twin-screw extruder at a barrel temperature of 180°C, a die temperature of 175°C, and a gap of 3mm to obtain the flame retardant core material of the middle layer.

[0069] The modified halogen-free flame retardant used in this preparation example is obtained from Preparation Example 1.

[0070] Preparation Example 9

[0071] The preparation steps of the flame-retardant core material of the middle layer are the same as those of Preparation Example 6, except that the modified halogen-free flame retardant used in this Preparation Example is obtained from Preparation Example 2.

[0072] Preparation Example 10

[0073] The preparation steps of the flame-retardant core material of the middle layer are the same as those of Preparation Example 6, except that the modified halogen-free flame retardant used in this Preparation Example is obtained from Preparation Example 3.

[0074] Preparation Example 11

[0075] The preparation steps of the flame-retardant core material of the middle layer are the same as those of Preparation Example 6, except that the modified halogen-free flame retardant used in this Preparation Example is obtained from Preparation Example 4.

[0076] Preparation Example 12

[0077] The preparation steps of the flame-retardant core material of the middle layer are the same as those of Preparation Example 6, except that the modified halogen-free flame retardant used in this Preparation Example is obtained from Preparation Example 5.

[0078] Preparation Example 13

[0079] The preparation steps of the flame retardant core material of the middle layer are the same as those of Preparation Example 6, except that in this Preparation Example, an equal amount of diethyl aluminum hypophosphite is used to replace the modified halogen-free flame retardant.

[0080] Preparation Example 14

[0081] The preparation steps of the modified penetrant are as follows:

[0082] Add 20g of isooctyl alcohol polyoxyethylene ether into the reactor, heat to 55°C, add 12.4mL of 12.5wt% dimethyldichlorosilane petroleum ether mixture, react at constant temperature for 1.2h, wash 5 times with 20wt% sodium hydroxide aqueous solution after rotary evaporation, add 12.5mL of 4wt% bentonite aqueous dispersion, disperse by ultrasonic, stir and react at 50°C for 10min, cool to room temperature, wash 3 times with deionized water and dry to obtain the modified penetrant.

[0083] Preparation Example 15

[0084] The preparation steps of the modified penetrant are the same as those of Preparation Example 14, except that 16 mL of a 12.5 wt % mixture of dimethyldichlorosilane and petroleum ether is added.

[0085] Preparation Example 16

[0086] The preparation steps of the modified penetrant were the same as those of Preparation Example 14, except that 65 mL of a 4 wt % aqueous dispersion of bentonite was added.

[0087] Preparation Example 17

[0088] The preparation steps of the special adhesive are as follows: mix 65g of ethylene-vinyl acetate copolymer, 3.5g of bisphenol A epoxy resin, 2.5g of styrene-maleic anhydride copolymer, 7.5g of nano titanium dioxide and 3g of paraffin, heat to 110°C, stir for 45 minutes, cool to 55°C, then add 3g of modified penetrant, 10g of rosin resin and 1.3g of antioxidant 168, heat to 80°C, stir for 75 minutes, transfer to a twin-screw extruder, heat to 175°C for melt extrusion and granulation to obtain the special adhesive.

[0089] The modified penetrant used in this preparation example was prepared by Preparation Example 14.

[0090] Preparation Example 18

[0091] The preparation steps of the special adhesive are as follows: mix 50g ethylene-vinyl acetate copolymer, 2g bisphenol A epoxy resin, 0.1g styrene-maleic anhydride copolymer, 5g nano titanium dioxide and 1g paraffin, heat to 100°C, stir for 30 minutes, cool to 50°C, then add 1g modified penetrant, 8g rosin resin and 0.5g antioxidant 168, heat to 70°C, stir for 60 minutes, transfer to a twin-screw extruder, heat to 170°C for melt extrusion and granulation to obtain the special adhesive.

[0092] The modified penetrant used in this preparation example was prepared by Preparation Example 14.

[0093] Preparation Example 19

[0094] The preparation steps of the special adhesive are as follows: 80g of ethylene-vinyl acetate copolymer, 5g of bisphenol A epoxy resin, 5g of styrene-maleic anhydride copolymer, 10g of nano titanium dioxide and 5g of paraffin are mixed, the temperature is raised to 120°C, stirred for 60 minutes, and then cooled to 60°C, 5g of modified penetrant, 12g of rosin resin and 2g of antioxidant 168 are added, the temperature is raised to 90°C, stirred for 90 minutes, transferred to a twin-screw extruder, and the temperature is raised to 180°C for melt extrusion and granulation to obtain the special adhesive.

[0095] The modified penetrant used in this preparation example was prepared by Preparation Example 14.

[0096] Preparation Example 20

[0097] The preparation steps of the special adhesive are the same as those of Preparation Example 17, except that the modified penetrant used is prepared by Preparation Example 15.

[0098] Preparation Example 21

[0099] The preparation steps of the special adhesive are the same as those of Preparation Example 17, except that the modified penetrant used is prepared by Preparation Example 16.

[0100] Preparation Example 22

[0101] The preparation steps of the special adhesive are the same as those of Preparation Example 17, except that the modified penetrant used is replaced by an equal amount of isooctyl alcohol polyoxyethylene ether.

[0102] Example 1

[0103] A preparation method of a high-performance flame-retardant aluminum composite panel comprises the following steps: coating the upper surface and the lower surface of the flame-retardant core material of the middle layer with a 0.25 mm thick special adhesive, covering an aluminum plate on the upper surface of the flame-retardant core material of the middle layer to form an upper aluminum plate, covering another aluminum plate on the lower surface of the flame-retardant core material of the middle layer to form a bottom aluminum plate, and then pressing for 45 seconds at room temperature and adjusting the pressure to 55 MPa, then heating to 350°C, adjusting the pressure to 200 MPa and pressing for 90 seconds, and cooling to room temperature while maintaining the pressure, so as to obtain a high-performance flame-retardant aluminum composite panel.

[0104] In this embodiment, the thickness of the flame retardant core material of the middle layer is 2.2 mm, and the thickness of the upper aluminum plate and the bottom aluminum plate are both 0.65 mm.

[0105] The flame-retardant core material of the middle layer used in this embodiment is prepared by Preparation Example 6, and the special adhesive used is obtained by Preparation Example 17.

[0106] Example 2

[0107] A preparation method of a high-performance flame-retardant aluminum composite panel comprises the following steps: coating the upper surface and the lower surface of the flame-retardant core material of the middle layer with a 0.3 mm thick special adhesive, covering an aluminum plate on the upper surface of the flame-retardant core material of the middle layer to form an upper aluminum plate, covering another aluminum plate on the lower surface of the flame-retardant core material of the middle layer to form a bottom aluminum plate, and then pressing for 60 seconds at room temperature and adjusting the pressure to 50 MPa, then heating to 200°C, pressing for 120 seconds at an adjusted pressure of 100 MPa, and cooling to room temperature while maintaining the pressure, so as to obtain a high-performance flame-retardant aluminum composite panel.

[0108] In this embodiment, the thickness of the flame retardant core material of the middle layer is 1.4 mm, and the thickness of the upper aluminum plate and the bottom aluminum plate are both 0.5 mm.

[0109] The flame-retardant core material of the middle layer used in this embodiment is prepared by Preparation Example 7, and the special adhesive used is obtained by Preparation Example 18.

[0110] Example 3

[0111] A preparation method of a high-performance flame-retardant aluminum composite panel comprises the following steps: coating the upper surface and the lower surface of the flame-retardant core material of the middle layer with a 0.2 mm thick special adhesive, covering an aluminum plate on the upper surface of the flame-retardant core material of the middle layer to form an upper aluminum plate, covering another aluminum plate on the lower surface of the flame-retardant core material of the middle layer to form a bottom aluminum plate, and then pressing for 30 seconds at room temperature and adjusting the pressure to 80 MPa, then heating to 500°C, pressing for 60 seconds at an adjusted pressure of 300 MPa, and cooling to room temperature while maintaining the pressure, so as to obtain a high-performance flame-retardant aluminum composite panel.

[0112] In this embodiment, the thickness of the flame retardant core material of the middle layer is 3 mm, and the thickness of the upper aluminum plate and the bottom aluminum plate are both 0.8 mm.

[0113] The flame-retardant core material of the middle layer used in this embodiment is prepared by Preparation Example 8, and the special adhesive used is obtained by Preparation Example 19.

[0114] Example 4

[0115] A method for preparing a high-performance flame-retardant aluminum composite panel, the specific implementation method is the same as Example 1, except that the flame-retardant core material of the middle layer is prepared by Preparation Example 9.

[0116] Example 5

[0117] A method for preparing a high-performance flame-retardant aluminum composite panel, the specific implementation method is the same as Example 1, except that the flame-retardant core material of the middle layer is prepared by Preparation Example 10.

[0118] Example 6

[0119] A method for preparing a high-performance flame-retardant aluminum composite panel, the specific implementation method is the same as Example 1, except that the flame-retardant core material of the middle layer is prepared by Preparation Example 11.

[0120] Example 7

[0121] A method for preparing a high-performance flame-retardant aluminum composite panel, the specific implementation method is the same as Example 1, the difference is that the flame-retardant core material of the middle layer used is prepared by Preparation Example 12.

[0122] Example 8

[0123] A method for preparing a high-performance flame-retardant aluminum composite panel, the specific implementation method is the same as Example 1, the difference is that the special adhesive used is prepared by Preparation Example 20.

[0124] Example 9

[0125] A method for preparing a high-performance flame-retardant aluminum composite panel, the specific implementation method is the same as Example 1, the difference is that the special adhesive used is prepared by Preparation Example 21.

[0126] Example 10

[0127] A method for preparing a high-performance flame-retardant aluminum composite panel, the specific implementation method is the same as Example 1, the difference is that the special adhesive used is prepared by Preparation Example 22.

[0128] Embodiment 11

[0129] A method for preparing a high-performance flame-retardant aluminum composite panel, the specific implementation method is the same as Example 1, except that the flame-retardant core material of the middle layer used is prepared by Preparation Example 13.

[0130] Performance Test:

[0131] The aluminum composite panels prepared in the above examples 1-11 were subjected to the following performance tests, and the specific test results are shown in Table 1:

[0132] (1) Flame retardant performance test: According to the standard GB / T20284-2006 "Single combustion test of building materials or products" (equivalent to EN13823), each aluminum composite panel is subjected to SBI test;

[0133] (2) Peeling performance test: According to the standard GB / T2790-1995 "Adhesive 180° Peel Strength Test Method - Flexible Material to Rigid Material", each aluminum composite panel is tested for peeling performance. The greater the peeling strength, the better the bonding performance;

[0134] (3) Stability test: According to the method disclosed in the invention patent CN116355556B, a high and low temperature transition test was performed on each aluminum composite panel to characterize the stability of the aluminum composite panel and observe whether the appearance is flat, whether there is local bulging or large-area bulging.

[0135] Table 1

[0136] project Flame retardant properties Peel strength / N / cm Whether it is bulging Example 1 88.5 25 smooth Example 2 86.5 24 smooth Example 3 87.6 22 smooth Example 4 85.3 21 smooth Example 5 85.7 20 smooth Example 6 84.0 20 smooth Example 7 83.2 19 smooth Example 8 86.8 17 smooth Example 9 87.0 16 Local bulge Example 10 86.4 14 Large area bulge Embodiment 11 81.7 18 Local bulge

[0137] As can be seen from Table 1, the combustion performance of the aluminum composite panels provided in Examples 1 to 3 of the present invention all meet the national standard B-s1, d0, and have a high fire resistance level. At the same time, the aluminum composite panels have high interlayer adhesion, high 180° peel strength, good stability, and high appearance flatness.

[0138] By comparing Examples 4-7 with Example 1, it can be seen that when preparing the modified halogen-free flame retardant of the flame-retardant core material of the intermediate layer, changing the addition ratio of diethyl aluminum hypophosphite and organic siloxane, changing the addition ratio of methyltriethoxysilane and tetraethoxysilane of organic siloxane, and adding only methyltriethoxysilane and tetraethoxysilane to prepare the modified halogen-free flame retardant, all of which will lead to different degrees of decrease in the flame retardant properties of the aluminum composite panel;

[0139] By comparing Examples 8 and 9 with Example 1, it can be seen that when the modified penetrant used in the special adhesive is added, changing the amount of the petroleum ether mixture of dimethyldichlorosilane and the aqueous dispersion of bentonite will lead to a decrease in the bonding strength and stability of the aluminum composite panel;

[0140] By comparing Example 10 with Example 1, it can be seen that when the modified penetrant used is replaced by isooctyl alcohol polyoxyethylene ether in equal amounts, the bonding strength between the layers of the aluminum composite plate is insufficient due to the penetration and viscosity of the special adhesive, which affects the stability and also causes large-area bulging and deformation in appearance;

[0141] By comparing Example 11 with Example 1, it can be seen that when diethyl aluminum hypophosphite is used in an equal amount to replace the modified halogen-free flame retardant to prepare the flame retardant core material of the intermediate layer used in the present invention, on the one hand, the flame retardant effect is affected, and on the other hand, the interlayer bonding strength and stability of the aluminum composite plate are also affected, resulting in a decrease in the comprehensive performance of the aluminum composite plate to varying degrees.

[0142] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A high performance flame retardant aluminum composite panel, characterized in that: The aluminum composite panel comprises, from top to bottom, an upper aluminum plate, a middle flame-retardant core material, and a bottom aluminum plate, and each layer is bonded by a special adhesive; wherein the upper aluminum plate and the bottom aluminum plate are both aluminum alloy plates with a thickness of 0.5 to 0.8 mm.

2. The high performance flame retardant aluminum composite panel according to claim 1, characterized in that: The flame retardant core material of the middle layer comprises the following raw materials in parts by weight: 40-60 parts of polypropylene, 20-35 parts of modified halogen-free flame retardant, 0.5-3 parts of antioxidant 168, 0.1-2 parts of foaming agent, and 0.5-1 part of dispersant.

3. The high performance flame retardant aluminum composite panel according to claim 2, characterized in that: The preparation steps of the modified halogen-free flame retardant are as follows: Add anhydrous ethanol and deionized water into the reactor, then add diethyl aluminum hypophosphite, stir and disperse, adjust the pH to 9-10, then add organosiloxane, heat to 40-60° C. under stirring, react for 1-3 hours, filter, wash, extract and dry the filtrate to obtain the modified halogen-free flame retardant.

4. The high performance flame retardant aluminum composite panel according to claim 3, characterized in that: The organosiloxane is a mixture of methyltriethoxysilane and tetraethoxysilane.

5. The high performance flame retardant aluminum composite panel according to claim 3, characterized in that: The mass ratio of the diethyl aluminum hypophosphite to the organosiloxane is 10:(3-6).

6. The high performance flame retardant aluminum composite panel according to claim 1, characterized in that: The special adhesive comprises the following raw materials in parts by weight: 50-80 parts of ethylene-vinyl acetate copolymer, 2-5 parts of bisphenol A epoxy resin, 0.1-5 parts of styrene-maleic anhydride copolymer, 8-12 parts of rosin resin, 1-5 parts of paraffin wax, 5-10 parts of nano titanium dioxide, 0.5-2 parts of antioxidant 168 and 1-5 parts of modified penetrant.

7. The high performance flame retardant aluminum composite panel according to claim 6, characterized in that: The preparation steps of the modified penetrant are as follows: Add isooctyl alcohol polyoxyethylene ether into the reactor, heat to 50-60° C., then add a mixture of dimethyldichlorosilane and petroleum ether, react at a constant temperature for 1-1.5 hours, perform rotary evaporation and alkaline water washing, mix with a water dispersion of bentonite, perform ultrasonic dispersion, react at 40-60° C. with stirring for 5-15 minutes, cool to room temperature, wash with deionized water, and dry to obtain the modified penetrant.

8. The high performance flame retardant aluminum composite panel according to claim 7, characterized in that: The mass ratio of dimethyldichlorosilane in the petroleum ether mixed solution of isooctyl alcohol polyoxyethylene ether and dimethyldichlorosilane is 20:(1.4-1.7).

9. The high performance flame retardant aluminum composite panel according to claim 7, characterized in that: The mass ratio of the isooctyl alcohol polyoxyethylene ether to the bentonite in the aqueous dispersion of bentonite is 10:(0.6-1).

10. A method for preparing a high-performance flame-retardant aluminum composite panel according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: coating the upper and lower surfaces of the flame-retardant core material of the middle layer with a special adhesive, covering an aluminum plate on the upper surface of the flame-retardant core material of the middle layer to form an upper aluminum plate, covering another aluminum plate on the lower surface of the flame-retardant core material of the middle layer to form a bottom aluminum plate, and then performing hot pressing and compounding to obtain the high-performance flame-retardant aluminum composite panel.